Blood conservation in cardiac surgery. Issue 2 (21st September 2017) - Blaudszun, G.; Butchart, A.; Klein, A. A.
SUMMARY: This article aims at reviewing the currently available evidence about blood conservation strategies in cardiac surgery. Pre‐operative anaemia and perioperative allogeneic blood transfusions are associated with worse outcomes after surgery. In addition, transfusions are a scarce and costly resource. As cardiac surgery accounts for a significant proportion of all blood products transfused, efforts should be made to decrease the risk of perioperative transfusion. Pre‐operative strategies focus on the detection and treatment of anaemia. The management of haematological abnormalities, most frequently functional iron deficiency, is a matter for debate. However, iron supplementation therapy is increasingly commonly administered. Intra‐operatively, antifibrinolytics should be routinely used, whereas the cardiopulmonary bypass strategy should be adapted to minimise haemodilution secondary to circuit priming. There is less evidence to recommend minimally invasive surgery. Cell salvage and point‐of‐care tests should also be a part of the routine care. Post‐operatively, any unnecessary iatrogenic blood loss should be avoided.